Geguritan Darma Kusuma: Pendekatan Sosial Sastra - Adelina Dewi, Ni Made; Ngurah Sulibra, I Ketut; Duana Sutika, I Nyoman (Humanis, 2016)
This study discusses the text Geguritan Darma Kusuma, the social analysis of literature. This study uses the theory of St ructural and Social Literature. This analysis aims to reveal the structure of the building works of the literary and social aspects contained in the geguritan. The methods and techniques used in this study were divided into three stages namely, (1) methods and techniques providing data used methods see and interview method assisted with recording technique and note (2) methods and techniques of data analysis using qualitative methods, techniques descriptive-analytic , (3) presentation of the methods and techniques used informal methods of data analaisis assisted with indukif-deductive techniques. The results obtained from this study is unfolding narrative structure comprising: an incident, plot, character and characterization, setting, theme and mandate. Besides this research reveals the social aspects consisting of: religious aspects, covering the aspects of philosophy (Tatwa) contained the teachings of Tri Hita Karana, and ethics to discuss the teachings of Tri Kaya Parisudha, aspects of loyalty there is teaching of Panca Satya, aspects of knowledge (education) by sage Utangka about the teaching of literature, and reminiscent of the teachings of Tri Kaya Parisudha, aspects of leadership which is owned by Darma Kusuma and Arjuna, and aspects of the magical herein is intended to achieve a good purpose, when a voice (word) from the sky that guides the Pandavas not commit self-immolation.